Adaptive frequency adjustment technique in current mode DC–DC converters for input voltage range extension. Issue 3 (25th January 2019) - Xiao, Zhiming; Zhao, Guangshu; Wang, Yu; Wang, Huashu; Hu, Weibo
Abstract : This study presents a switching frequency adjustment technique that helps widen the input voltage range of a current mode DC–DC converter. Conventional current‐mode switching converters suffer the minimum on/off time restrictions that limit the input‐to‐output conversion ratio. This work introduces an additional regulation loop on top of an existing converter that regulates the switching period when the minimum on/off time limit is approached. Compared with a converter with fixed switching frequency, the proposed approach allows the free‐running switching to be set without being limited by the minimum on/off time. A boost topology with output voltage of 24 V was built based on the proposed approach, and the measured valid input voltage range was extended from 8–16 to 3–21 V by the proposed scheme under 1 MHz preset frequency. Since the slope‐compensation current, the inductor size, and the output capacitor are all optimised at 1 MHz and is not limited by the minimum on/off time which may lower the switching frequency of a conventional converter down to 450 kHz, the measured maximum available output current and the typical output voltage ripple under 12 V input achieved 1.57 A and 57 mV, respectively.